Capric acid-myristyl alcohol phase change material as well as preparation method and application thereof

By using composite phase change materials prepared by capric acid and myristyl alcohol, the problems of low thermal conductivity and poor stability of existing phase change materials are solved, and a wider phase change temperature range and better thermal characteristics are achieved, which are suitable for underground energy structures.

CN119505819APending Publication Date: 2025-02-25CHONGQING UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411617284.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing phase change materials have problems of low thermal conductivity and poor stability, which are difficult to meet the needs of different phase change temperatures.

Method used

A binary eutectic mixture is prepared by mixing heat treatment and impregnation methods using capric acid and myristyl alcohol as raw materials, and adsorbed it into hollow open steel balls. After cooling, drying and packaging, a capric acid-myristyl alcohol composite phase change material is prepared.

Benefits of technology

It effectively broadens the phase change temperature range, maintains the good thermal characteristics of a single component, conforms to the working environment of the underground energy structure, and reduces the leakage of phase change materials through HSB packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505819A_ABST
    Figure CN119505819A_ABST
Patent Text Reader

Abstract

The invention discloses a decanoic acid-myristyl alcohol phase change material as well as a preparation method and application thereof, and belongs to the technical field of energy storage phase change materials. The preparation method comprises the following steps: firstly, mixing capric acid and myristyl alcohol, carrying out heat treatment to prepare a binary eutectic mixture, then adsorbing the obtained binary eutectic mixture into hollow open steel balls through an impregnation method, cooling, drying, and finally packaging to obtain the hollow open steel balls. The phase-change temperature range of the prepared composite phase-change material is 18.30-20.86 DEG C. Compared with the phase-change temperature of a traditional phase-change material, the phase-change temperature range suitable for organic matters is effectively widened, good thermal characteristics of a single component are kept, the composite phase-change material better conforms to the working environment of an underground energy structure, and the working efficiency is improved. Meanwhile, the graphite powder is doped, so that a plurality of heat conduction channels are formed in the phase-change concrete, and the heat exchange capacity of the phase-change concrete is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of energy storage phase change materials, and in particular to a capric acid-myristyl alcohol phase change material and a preparation method and application thereof. Background Art

[0002] Energy is the basis of human survival and development. With the development of science and technology, human demand for energy is increasing. Thermal storage materials are generally divided into three categories according to the way of energy storage: sensible heat storage, latent heat storage and chemical reaction storage. Although sensible heat storage materials are relatively simple and convenient to use, their application value is not high; chemical reaction energy storage uses the reaction heat of reversible chemical reactions to store energy, but the technology is complex and inconvenient to use; latent heat storage uses the heat absorption and release of materials during phase change to store or store energy. Among these three categories of energy storage materials, latent heat storage has the most practical development prospects and is also the most widely used and important energy storage method. It has the characteristics of high heat storage density, approximately isothermal heat storage and heat release, and easy process control. In the latent heat storage system, when the phase change material undergoes a phase change process at a continuous temperature, it absorbs or releases heat equivalent to its latent heat.

[0003] Phase change temperature is an important indicator in the field of phase change thermal storage. It is particularly important to adapt phase change materials to different temperatures based on different application environments. However, commonly used fatty acids and fatty alcohols often have only carbon numbers of C12-C18, which leads to a small applicable phase change temperature range and a high phase change temperature, which seriously limits their application.

[0004] Single-component heat storage materials are difficult to meet the requirements for different phase change temperatures in practical applications, and pure organic phase change materials have disadvantages such as low thermal conductivity, volatility and flammability. How to prepare composite phase change materials with good thermal conductivity and stability and fully combine their physical and chemical properties is the technical difficulty of composite phase change materials. Summary of the invention

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a capric acid-myristyl alcohol phase change material and a preparation method and application thereof, so as to solve the problems of low thermal conductivity and poor stability of existing phase change materials.

[0006] The technical solution of the present invention to solve the above technical problems is as follows:

[0007] A method for preparing a capric acid-myristyl alcohol composite phase change material comprises the following steps:

[0008] Firstly, decanoic acid and myristyl alcohol are mixed and heat-treated to prepare a binary eutectic mixture, and then the binary eutectic mixture is adsorbed into a hollow open steel ball by an impregnation method, cooled and dried, and finally packaged to obtain the product.

[0009] The beneficial effects of the present invention are as follows: the present invention uses capric acid and myristyl alcohol as raw materials to prepare a composite phase change material, effectively broadens the phase change temperature range, and maintains the good properties of a single component, which is more in line with the working environment of an underground energy structure. At the same time, the HSB packaging method is adopted to effectively reduce the leakage of the phase change material.

[0010] Furthermore, the molar ratio of capric acid to myristyl alcohol is (60-70):(30-40).

[0011] Preferably, the molar ratio of capric acid to myristyl alcohol is 66.7:33.3.

[0012] Furthermore, the melting temperature, enthalpy and molar mass of decanoic acid are 31.5°C, 154 J / g and 172.27 g / mol, respectively; the melting temperature, enthalpy and molar mass of myristyl alcohol are 35-39°C, 150 J / g and 228.38 g / mol, respectively.

[0013] The beneficial effect of adopting the above further technical scheme is: the present invention obtains a binary low eutectic mixture material with a eutectic temperature of 19.76°C by optimizing the ratio of capric acid and myristic alcohol, which can effectively prolong the phase change process of capric acid, thereby more effectively maintaining a constant temperature environment.

[0014] Furthermore, the conditions for the mixed heat treatment are: heating in a water bath at 75-80° C. for 6-8 hours.

[0015] Furthermore, the conditions of the impregnation method are: first, under vacuum conditions, the hollow open steel ball is mixed with the binary eutectic mixture, and then vacuum suction is performed at a pressure of 0.4-0.6MPa to allow the binary eutectic mixture to penetrate into the interior of the hollow open steel ball, and finally, the mixture is allowed to stand for 3-5 hours and the remaining liquid is extracted.

[0016] Preferably, the conditions of the impregnation method are: first, under vacuum conditions, the hollow open steel ball is mixed with the binary eutectic mixture, and then vacuum suction is performed at a pressure of 0.5 MPa to allow the binary eutectic mixture to penetrate into the hollow open steel ball, and finally, the mixture is allowed to stand for 4 hours and the remaining liquid is extracted.

[0017] Furthermore, the inner diameter of the hollow open steel ball is 17-21 mm, the outer diameter is 18-22 mm, and the opening is 3-5 mm.

[0018] Preferably, the inner diameter of the hollow open steel ball is 19 mm, the outer diameter is 20 mm, and the opening is 4 mm.

[0019] Furthermore, the composite phase change material is cooled and dried by placing it in a constant temperature box under room temperature.

[0020] Furthermore, the packaging conditions are: first rivet packaging is performed, and then epoxy resin glue is used to fill the gaps in the packaging.

[0021] A capric acid-myristyl alcohol composite phase change material is prepared by adopting the above preparation method.

[0022] A method for preparing graphite powder / decanoic acid-myristyl alcohol phase change concrete comprises the following steps:

[0023] The process comprises mixing cement, graphite powder, sand, gravel, water and the above-mentioned composite phase change material as raw materials, pouring, curing and preparing the composite phase change material;

[0024] The raw materials consist of the following components in parts by weight: 460-490 parts of cement, 10-40 parts of graphite powder, 500-570 parts of sand, 840-960 parts of gravel, 180-250 parts of water and 169-338 parts of composite phase change material.

[0025] The beneficial effects of the present invention are as follows: the present invention effectively improves the specific heat capacity and heat storage capacity of concrete, improves the thermal conductivity of concrete, and ensures high mechanical properties of concrete by combining the decanoic acid-myristyl alcohol encapsulated composite phase change material with graphite powder.

[0026] Furthermore, the raw materials consist of the following parts by weight: 475 parts of cement, 25 parts of graphite powder, 538 parts of sand, 898 parts of gravel, 210 parts of water and 254 parts of composite phase change material.

[0027] Furthermore, the mixing time is 10-15 min.

[0028] Furthermore, during the pouring process, vibration equipment is used to remove air bubbles and ensure compactness.

[0029] Furthermore, during the curing process, the concrete surface is kept moist by covering it with a wet cloth or spraying a curing agent.

[0030] A graphite powder / decanoic acid-myristyl alcohol phase change concrete is prepared by adopting the preparation method.

[0031] The present invention has the following beneficial effects:

[0032] (1) The temperature range of the phase change material in the composite phase change material prepared by the present invention is 18.30-20.86°C. Compared with the phase change temperature of the traditional phase change material, it effectively broadens the phase change temperature range suitable for this type of organic matter and maintains the good thermal properties of the individual components, which is more in line with the working environment of the underground energy structure. At the same time, the HSB packaging method effectively reduces the leakage of the phase change material.

[0033] (2) Adding the composite phase change material prepared by the present invention to concrete can effectively increase the specific heat capacity of concrete, improve the heat storage capacity of concrete, and have little effect on the mechanical properties of concrete.

[0034] (3) The present invention can effectively improve the thermal conductivity of the phase change concrete by adding graphite powder, and the addition of graphite powder will not cause a significant decrease in the specific heat capacity of the phase change concrete, thereby ensuring that the phase change concrete has the characteristic of high specific heat capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 A flow chart for the preparation of a composite phase change material encapsulated with capric acid-myristyl alcohol;

[0036] Figure 2 This is a ratio diagram of graphite powder and decanoic acid-myristyl alcohol encapsulated composite phase change material in graphite powder / decanoic acid-myristyl alcohol phase change concrete;

[0037] Figure 3 It is a compressive strength diagram of different graphite powder and decanoic acid-myristyl alcohol encapsulated composite phase change material doping ratios in the test example;

[0038] Figure 4 is a graph of thermal conductivity at different doping ratios of graphite powder and decanoic acid-myristyl alcohol encapsulated composite phase change material in the test example;

[0039] Figure 5 These are the specific heat capacity test results of the graphite powder / decanoic acid-myristyl alcohol phase change concrete at the endothermic temperature and the exothermic temperature in the test example. DETAILED DESCRIPTION

[0040] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0041] Embodiment 1:

[0042] A method for preparing graphite powder / decanoic acid-myristyl alcohol phase change concrete comprises the following steps:

[0043] (1) Capric acid (CA) and myristyl alcohol (MA) were mixed in a container at a molar ratio of 66.7:33.3, and heated in a water bath at 80° C. for 7 h to obtain a binary eutectic mixture.

[0044] (2) The binary eutectic mixture prepared in step (1) was mixed with a hollow open steel ball (custom-made, with an inner diameter of 19 mm, an outer diameter of 20 mm, and an opening of 4 mm) and placed in a container, and then vacuum suction was performed at a pressure of 0.5 MPa to extract the gas from the hole of the hollow open steel ball, so that a negative pressure was formed in the hollow open steel ball, thereby promoting the container to penetrate into the interior of the sample. Subsequently, the sample was left to stand for 4 hours under vacuum conditions to allow the solution to penetrate into the interior of the sample, and then the remaining liquid was extracted.

[0045] (3) placing the steel ball finally processed in step (2) in a constant temperature box at room temperature for cooling and drying.

[0046] (4) The steel balls obtained after cooling and drying in step (3) are packaged. When packaging, the steel balls are first packaged manually by riveting with a rivet gun, and then the gaps in the packaging are filled with epoxy resin glue to ensure that the phase change material is firm and leak-free, thereby obtaining a composite phase change material (CA-MA-HSB). The preparation method is as follows: Figure 1 shown.

[0047] (5) According to the mix ratio of conventional concrete, the composite phase change material prepared in step (4) is used to replace 15% of the mass proportion of coarse aggregate in the conventional concrete (the coarse aggregate includes sand and gravel, each replaced by 15%), and graphite powder (GP) is used to replace 5% of the mass proportion of cement in the conventional concrete, such as Figure 2 shown.

[0048] The specific weight proportion of the replaced graphite powder / decanoic acid-myristyl alcohol phase change concrete is as follows:

[0049] 475 parts of cement, 25 parts of graphite powder, 538 parts of sand, 898 parts of gravel, 210 parts of water and 254 parts of encapsulated composite phase change material.

[0050] First, mix the raw materials according to the above ratio and pour them into a mixer for sufficient stirring for 12 minutes. Then pour the mixed concrete into the formwork to form the desired shape. During the pouring process, use vibration equipment to remove bubbles and ensure density. Finally, remove the mold, spray curing agent for maintenance, keep the concrete surface moist, thereby improving its strength and durability.

[0051] In this embodiment, the eutectic ratio is determined by calculating the Schrader equation of the eutectic theory. The Schrader equation of the eutectic theory is:

[0052]

[0053] Where i is the component of the binary eutectic mixture (CA-MA), T i is the phase transition temperature of the binary eutectic mixture, T is the eutectic temperature of the binary mixture, X iis the mole fraction of i, and R is the gas constant.

[0054] The melting temperature, enthalpy and molar mass of decanoic acid (CA) are 31.5°C, 154 J / g and 172.27 g / mol, respectively, and the melting temperature, enthalpy and molar mass of myristyl alcohol (MA) are 35-39°C, 150 J / g and 228.38 g / mol, respectively.

[0055] The calculation results of the Schrader equation in this embodiment are as follows: the theoretical eutectic temperature of CA-MA is 19.76° C., and the molar mass ratio of CA-MA is 66.7:33.3.

[0056] In order to verify whether this calculation method is feasible for determining the parameters of decanoic acid-myristyl alcohol (CA-MA) composite phase change materials, a step cooling curve test was carried out on the decanoic acid-myristyl alcohol (CA-MA) composite phase change material. The results showed that the phase change temperature of CA-MA was lower than that of MA. During the phase change process, the temperature change gradually slowed down, and an obvious temperature platform appeared, which lasted for about 2500s. This shows that the binary eutectic mixture can effectively prolong the phase change process of CA, thereby more effectively maintaining a constant temperature environment.

[0057] The DSC test was carried out on the decanoic acid-myristyl alcohol (CA-MA) composite phase change material. The heating process was carried out from 10℃ to 70℃ at a heating rate of 2℃ / min. The sample had a single endothermic peak with a sharp and smooth shape, which indicated that the sample was completely eutectic and stable. CA and MA were fused into a whole at this ratio. The mass ratio of the components of the sample was 67:33, which was consistent with the theoretically calculated mass ratio of the components, indicating that the Schrader equation was applicable.

[0058] Embodiment 2:

[0059] A method for preparing graphite powder / decanoic acid-myristyl alcohol phase change concrete comprises the following steps:

[0060] The preparation method is the same as that of Example 1, except that the content of graphite powder in step (5) is changed to 2.5% by mass of cement.

[0061] Embodiment 3:

[0062] A method for preparing graphite powder / decanoic acid-myristyl alcohol phase change concrete comprises the following steps:

[0063] The preparation method is the same as that of Example 1, except that the content of graphite powder in step (5) is changed to 7.5% by mass of cement.

[0064] Embodiment 4:

[0065] A method for preparing graphite powder / decanoic acid-myristyl alcohol phase change concrete comprises the following steps:

[0066] The preparation method is the same as that of Example 1, except that the content of the composite phase change material in step (5) is changed to 12.5% ​​by mass of coarse aggregate.

[0067] Embodiment 5:

[0068] A method for preparing graphite powder / decanoic acid-myristyl alcohol phase change concrete comprises the following steps:

[0069] The preparation method is the same as that of Example 4, except that the content of graphite powder in step (5) is changed to 2.5% by mass of cement.

[0070] Embodiment 6:

[0071] A method for preparing graphite powder / decanoic acid-myristyl alcohol phase change concrete comprises the following steps:

[0072] The preparation method is the same as that of Example 4, except that the content of graphite powder in step (5) is changed to 7.5% by mass of cement.

[0073] Embodiment 7:

[0074] A method for preparing graphite powder / decanoic acid-myristyl alcohol phase change concrete comprises the following steps:

[0075] The preparation method is the same as that of Example 1, except that the content of the composite phase change material in step (5) is changed to 10% by mass of coarse aggregate.

[0076] Embodiment 8:

[0077] A method for preparing graphite powder / decanoic acid-myristyl alcohol phase change concrete comprises the following steps:

[0078] The preparation method is the same as that of Example 7, except that the content of graphite powder in step (5) is changed to 2.5% by mass of cement.

[0079] Embodiment 9:

[0080] A method for preparing graphite powder / decanoic acid-myristyl alcohol phase change concrete comprises the following steps:

[0081] The preparation method is the same as that of Example 7, except that the content of graphite powder in step (5) is changed to 7.5% by mass of cement.

[0082] Comparative Example 1:

[0083] A method for preparing graphite powder / decanoic acid-myristyl alcohol phase change concrete comprises the following steps:

[0084] The preparation method is the same as that of Example 1, except that no graphite powder is added in step (5).

[0085] Comparative Example 2:

[0086] A method for preparing graphite powder / decanoic acid-myristyl alcohol phase change concrete comprises the following steps:

[0087] The preparation method is the same as that of Example 4, except that no graphite powder is added in step (5).

[0088] Comparative Example 3:

[0089] A method for preparing graphite powder / decanoic acid-myristyl alcohol phase change concrete comprises the following steps:

[0090] The preparation method is the same as that of Example 7, except that no graphite powder is added in step (5).

[0091] Comparative Example 4:

[0092] A method for preparing graphite powder / decanoic acid-myristyl alcohol phase change concrete comprises the following steps:

[0093] The preparation method is the same as that of Example 1, except that the content of graphite powder in step (5) is changed to 10% by mass of cement.

[0094] Comparative Example 5:

[0095] A method for preparing graphite powder / decanoic acid-myristyl alcohol phase change concrete comprises the following steps:

[0096] The preparation method is the same as that of Example 4, except that the content of graphite powder in step (5) is changed to 10% by mass of cement.

[0097] Comparative Example 6:

[0098] A method for preparing graphite powder / decanoic acid-myristyl alcohol phase change concrete comprises the following steps:

[0099] The preparation method is the same as that of Example 7, except that the content of graphite powder in step (5) is changed to 10% by mass of cement.

[0100] Test example:

[0101] A WDAJ rock shear rheology testing machine was used to load in a displacement controlled manner at a test loading rate of 0.3 mm / min to measure the compressive strength of the concrete prepared in Examples 1-9 and Comparative Examples 1-6.

[0102] The results of the test are as follows Figure 3As shown, the increase in the addition of graphite powder (GP) and decanoic acid-myristyl alcohol (CA-MA) composite phase change material will lead to a decrease in the compressive strength of the graphite powder / decanoic acid-myristyl alcohol (GP / CA-MA-HSB) phase change concrete. However, when the decanoic acid-myristyl alcohol encapsulated (CA-MA-HSB) composite phase change material is used to replace 15% of the coarse aggregate in the graphite powder / decanoic acid-myristyl alcohol (GP / CA-MA-HSB) phase change concrete by mass, and when the graphite powder (GP) is used to replace 5% of the cement in the concrete by mass, the compressive strength of the graphite powder / decanoic acid-myristyl alcohol (GP / CA-MA-HSB) phase change concrete (Example 1) still meets the compressive strength standard value of C30 concrete, which is the best embodiment of the present application. However, the concrete prepared in Comparative Examples 4-6 has a lower compressive strength due to the excessive addition of graphite powder.

[0103] The thermal conductivity of the concretes prepared in Examples 1-9 and Comparative Examples 1-6 was measured by a rapid thermal conductivity meter using a hot wire method.

[0104] The results of the test are as follows Figure 4 As shown, the results show that the concrete obtained by comparative examples 1-3 without adding graphite powder has a significantly lower thermal conductivity than other embodiments. This is because the sample is at room temperature before the test, and the concrete is heated by the substrate, so that the temperature of the decanoic acid-myristyl alcohol composite phase change material is increased and heat energy is absorbed, which reduces the heat flux in the thickness direction of the graphite powder / decanoic acid-myristyl alcohol phase change concrete, and reduces the thermal conductivity. It shows that the incorporation of decanoic acid-myristyl alcohol composite phase change material reduces the thermal conductivity of concrete. Graphite powder also changes the thermal conductivity of concrete, and its influence is much greater than that of decanoic acid-myristyl alcohol encapsulated composite phase change material. When the specific gravity of graphite powder reaches a certain content, the arrangement between the graphite powders is close to form a continuous heat conduction channel. Because the heat conduction process follows the principle of thermal resistance in series, the heat conduction channel allows heat to be transferred quickly, thereby improving the thermal conductivity of concrete. The thermal conductivity of Example 3 is 5.53% higher than that of Example 1, and the thermal conductivity of Example 7 is 26.37% higher than that of Example 8, indicating that when the content of graphite powder reaches 5%, closely arranged and continuous heat conduction channels have been formed between the graphite powders. Increasing the content of graphite powder further weakens the ability to improve the thermal conductivity of graphite powder / decanoic acid-myristyl alcohol phase change concrete. Therefore, the optimal content of graphite powder is 5%.

[0105] The specific heat capacity test results of the graphite powder / decanoic acid-myristyl alcohol phase change concrete prepared in Example 1, Example 4 and Example 7 at the endothermic temperature (sample temperature>20°C) and the exothermic temperature (sample temperature<20°C) are as follows: Figure 5As shown. Regardless of endothermic conditions or exothermic conditions, the specific heat capacity of the graphite powder / decanoic acid-myristyl alcohol phase change concrete increases with the increase of the decanoic acid-myristyl alcohol composite phase change material, so the optimal content of the decanoic acid-myristyl alcohol composite phase change material in the present invention is 15%.

[0106] Based on the above analysis of compressive strength, thermal conductivity and specific heat capacity, it is determined that the proportion of decanoic acid-myristyl alcohol composite phase change material in the coarse aggregate mass in concrete is 15%, and the proportion of graphite powder in the cement mass in concrete is 5%, that is, Example 1, which is the best embodiment of the present invention.

[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a capric acid-myristyl alcohol composite phase change material, characterized in that: The following steps are involved: Firstly, decanoic acid and myristyl alcohol are mixed and heat-treated to prepare a binary eutectic mixture, and then the binary eutectic mixture is adsorbed into a hollow open steel ball by an impregnation method, cooled and dried, and finally packaged to obtain the product.

2. The method for preparing the capric acid-myristyl alcohol composite phase change material according to claim 1, characterized in that: The molar ratio of capric acid to myristyl alcohol is (60-70):(30-40).

3. The method for preparing the capric acid-myristyl alcohol composite phase change material according to claim 1, characterized in that: The conditions of the mixed heat treatment are: heating in a water bath at 75-80° C. for 6-8 hours.

4. The method for preparing the capric acid-myristyl alcohol composite phase change material according to claim 1, characterized in that: The conditions of the impregnation method are: first, under vacuum conditions, the hollow open steel ball is mixed with the binary eutectic mixture, and then vacuum suction is performed at a pressure of 0.4-0.6 MPa to allow the binary eutectic mixture to penetrate into the hollow open steel ball, and finally, the mixture is allowed to stand for 3-5 hours and the remaining liquid is extracted.

5. The method for preparing the capric acid-myristyl alcohol composite phase change material according to claim 1 or 4, characterized in that: The inner diameter of the hollow open steel ball is 17-21 mm, the outer diameter is 18-22 mm, and the opening is 3-5 mm.

6. The method for preparing the capric acid-myristyl alcohol composite phase change material according to claim 1, characterized in that: The packaging conditions are as follows: firstly rivet packaging is performed, and then epoxy resin glue is used to fill the gaps in the packaging.

7. A capric acid-myristyl alcohol composite phase change material, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 6.

8. A method for preparing graphite powder / decanoic acid-myristyl alcohol phase change concrete, characterized in that: The following steps are involved: The composite phase change material according to claim 7 is prepared by mixing cement, graphite powder, sand, gravel, water and the composite phase change material as raw materials, pouring, curing and so on; The raw materials consist of the following components in parts by weight: 460-490 parts of cement, 10-40 parts of graphite powder, 500-570 parts of sand, 840-960 parts of gravel, 180-250 parts of water and 169-338 parts of composite phase change material.

9. The method for preparing graphite powder / decanoic acid-myristyl alcohol phase change concrete according to claim 8, characterized in that: The raw materials in step (2) are composed of the following parts by weight: 475 parts of cement, 25 parts of graphite powder, 538 parts of sand, 898 parts of gravel, 210 parts of water and 254 parts of composite phase change material.

10. A graphite powder / decanoic acid-myristyl alcohol phase change concrete, characterized in that: The method is prepared according to claim 8 or 9.

Citation Information

Cited By

  • Phase change material loaded steel fiber and preparation method and application thereof

    CN120328899A